Influence of exposed facets, morphology and hetero-interfaces of BiVO4 on photocatalytic water oxidation: A review. (18th June 2021) - Rather, Rayees Ahmad; Mehta, Akansha; Lu, Youming; Valant, Matjaz; Fang, Ming; Liu, Wenjun
Abstract: The photocatalytic water splitting has a stupendous role to generate renewable hydrogen. However, the overall water splitting reaction is limited by the sluggish oxidation step. Bismuth vanadate (BiVO4 ) has been identified as one of the most promising n-type semiconductors for photocatalytic water oxidation due to its small energy gap and favorable band alignment. Thus, it is necessary to summarize the recent progress done on BiVO4 for the guidance of future research. In this review, we have discussed recent strategies that have been adopted to boost its photoconversion efficiency at three different levels: (1) facet control, (2) morphological control and, (3) interfacial control. The roles of high indexed facets, anisotropic morphologies, and mediator-based Z schemes are comprehensively discussed and the emphasis is given to find the suitable structural, morphological, and interfacial combination of BiVO4 for efficient water oxidation. Highlights: Elaboration of strategies to enhance the efficiency of BiVO4 for water oxidation. Correlation of structural, morphology and interfacial characteristics with activity. Outline of unique prospective for future research.